Bolus injections of novel thrombogenic site-targeted fusion proteins comprising annexin-V and Kunitz protease inhibitors attenuate intimal hyperplasia after balloon angioplasty. (1st August 2017) - Yeh, Yung-Hsin; Chang, Shang-Hung; Chen, Shin-Yu; Wen, Chih-Jen; Wei, Fu-Chan; Tang, Rui; Achilefu, Sam; Wun, Tze-Chein; Chen, Wei-Jan
Abstract: Background: Systemic administrations of conventional antithrombotics reduce neointima formation after angioplasty in experimental animals. However, clinical translation of these results has not been successful due to high risk for bleeding. Objectives: We sought to determine whether novel annexin-V (ANV)-Kunitz protease inhibitor fusion proteins, TAP-ANV and ANV-6L15, can specifically target to vascular injury site and limit neointima formation without inducing systemic hypo-coagulation in a rat carotid artery balloon angioplasty injury model. Methods: Near infrared imaging was carried out after balloon-injury and injection of fluorescent ANV or ANV-6L15 to examine their bio-distributions. For peri-procedure treatment, TAP-ANV or ANV-6L15 was administered as i.v. boluses 3 times: 30-minutes before balloon-injury, immediate after procedure, and 120-minutes post-balloon-injury. For extended treatment, additional i.v. bolus injection was given on day-2, day-3 and every other day thereafter. Carotid arteries were collected on day-7 and day-14 for analysis. Blood was collected for measurement of clotting parameters. Results: Near infrared imaging and immunochemistry showed that fluorescent ANV and ANV-6L15 specifically localized to injured carotid artery and significant amount of ANV-6L15 remained bound to the injured artery after 24-h. Peri-procedure injections of TAP-ANV or ANV-6L15 resulted in decrease of intima/media ratio by 56%. Extended injections of both yielded similar results. Both decreased the expression of PCNA on day-7 and increased the expression calponin on day-14 in the intima post-balloon-injury. Conclusions: TAP-ANV and ANV-6L15 can specifically localize to balloon injured carotid arteries after i.v. bolus injections, resulting in substantial attenuation of intimal hyperplasia without inducing a state of systemic hypo-coagulation.